Mobile Apps Foster Student Self-Awareness and Empathy in Technology Education : Aplikasi Mobile Menumbuhkan Kesadaran Diri dan Empati Siswa dalam Pendidikan Teknologi - Hermansyah, David; Aqodiah, Aqodiah; Astini, Baiq Ida; Said, Khaeruddin; Mappanyompa, Mappanyompa; Ali , Mustapa (Pedagogia : Jurnal Pendidikan, 2025)
This study aims to investigate the effectiveness of using mobile applications in fostering self-awareness and empathy among students in the context of character education. The research method used is quantitative with a survey approach. The research subjects consist of 48 students and 14 teachers from elementary, middle, and high school levels. The research instrument used is a Likert Scale questionnaire, consisting of 14 items for teachers and 20 items for students. Data analysis was conducted using a t-test, which showed that there was no significant difference between the responses given by teachers and students regarding the use of mobile applications in developing self-awareness and empathy. Similarly, there was no significant difference between male and female students in terms of their responses to the application. This research provides an important contribution to the understanding of the potential use of technology, particularly mobile applications, in the context of character education. The practical implication of this study is that educators can utilize mobile applications as an effective tool in shaping students' character, regardless of gender. Further research can deepen the understanding of the factors influencing responses to mobile applications and explore more specific strategies for implementing character education through technology.